A critical appraisal of microemulsions for drug delivery: part I. (December 2013) - Sapra, Bharti; Thatai, Purva; Bhandari, Sameer; Sood, Jatin; Jindal, Manish; Tiwary, Ashok
Microemulsions (MEs) are thermodynamically stable, optically transparent isotropic solutions of oil and water successfully formulated by using a combination of suitable surfactant and cosurfactant. While the selection of oil is based primarily on the solubility of drug in it, surfactant is generally selected on the basis of its hydrophilic–lipophilic balance value. MEs are characterized by ultra-low interfacial tension between the immiscible phases and offer the advantage of spontaneous formation, thermodynamic stability and ease of manufacture. The solubilization power of MEs for lipophilic, hydrophilic and amphiphilic solutes form a viable approach for enhancing bioavailability of hydrophobic drugs and percutaneous permeation of poorly permeable drugs, mainly due to the large area to volume ratio available for mass transfer.